51 new pre-breeding wheat lines with high yield potential and climate resilience for Mexico - CGIAR Research Program on Wheat (2019)
51 new pre-breeding wheat lines showed greater yield potential and climate resilience. The lines show high yield potential and resilience to heat and drought impacted conditions, but have not yet been piloted.